Socioecological systems analysis of potential factors for cholera outbreaks and assessment of health system's readiness to detect and respond in Ilemela and Nkasi districts, Tanzania - Baraka L. Ngingo; Zaina S. Mchome; Veneranda M. Bwana; Augustino Chengula; Gaspary Mwanyika; Irene Mremi; Calvin Sindato; Leonard E.G. Mboera (BMC, 2023)
Abstract Background Cholera outbreaks are a recurrent issue in Tanzania, with Ilemela and Nkasi districts being particulary affected. The objective of this study was to conduct a socio-ecological system (SES) analysis of cholera outbreaks in these districts, identifying potential factors and assessing the preparedness for cholera prevention and control. Methods A cross-sectional study was carried out in Ilemela and Nkasi districts of Mwanza and Rukwa regions, respectively in Tanzania between September and October 2021. A SES framework analysis was applied to identify potential factors associated with cholera outbreaks and assess the readiness of the districts to cholera prevention and control. Results Ilemela is characterised by urban and peri-urban ecosystems while Nkasi is mainly rural. Cholera was reported to disproportionately affect people living along the shores of Lake Victoria in Ilemela and Lake Tanganyika in Nkasi, particularly fishermen and women involved infish trading. The main potential factors identified for cholera outbreaks included defecation in the shallow ends and along the edges of lakes, open defecation, bathing/swimming in contaminated waters and improper waste disposal. The preparedness of both districts for cholera prevention and response was found to be inadequate due to limited laboratory capacity, insufficient human resources, and budget constraints. Conclusion People of Ilemela and Nkasi districts remain at significant risk of recurrent cholera outbreaks and the capacity of the districts to detect the disease is limited. Urgent preventive measures, such as conducting considerable community awareness campaigns on personal hygiene and environmental sanitation are needed to alleviate the disease burden and reduce future cholera outbreaks.